Validity through dialogue - Cambridge, Barbara (Teaching and Learning Inquiry, 2013)
Teaching & Learning Inquiry takes responsibility for engaging in what Senge (2006) calls “reflective openness,” encouraging a range of appropriate epistemologies to study teaching and learning. The journal, like its parent organization, embodies the role of “intermediary” through the practice of continual examination of ideas and the provisions of “stability, expert depth, and fieldwide reach” (Bacchetti & Ehrlich, 2006) for the Scholarship of Teaching and Learning.